Ion chromatography tandem mass spectrometry (IC-MS/MS) multimethod for the determination of highly polar pesticides in plant-derived commodities. (April 2018) - Bauer, Anna; Luetjohann, Jens; Rohn, Sascha; Kuballa, Jürgen; Jantzen, Eckard
Abstract: A new sensitive, fast, and robust analytical method based on a QuPPe (Quick Polar Pesticides) extraction procedure coupled to ion chromatography-tandem mass spectrometry (IC-MS/MS) was developed. The study aimed at the determination of the highly polar pesticides chlorate, perchlorate, ethephon, and 2-hydroxyethylphosphonic acid (HEPA) in different plant food commodities. For achieving an acceptable dynamic range for chlorate and perchlorate and to compensate for matrix effects, the isotopically-labelled internal standards 18 O3 -chlorate and 18 O4 -perchlorate and ethephon D4 were applied for calibration. The optimized method was fully validated at levels of 0.010 and 0.100 mg kg −1 for all compounds in the matrices tomato, apple, lemon, sultana, avocado, and wheat according to the actual EU guidance document SANTE/11945/2015. For HEPA and the commodity sultana levels for validation were chosen at 0.050 mg kg −1 and 0.100 mg kg −1 . The precision and accuracy of the validation results were determined at hand of five replicates with recovery rates between 93 and 119% and RSDs between 1 and 14%. The use of internal standards for chlorate, perchlorate and ethephon allows the determination in a wide working range between 0.01 and 1 mg kg −1 without interference by matrix effects. The developed analytical methodology is able to meet the strict requirements for the analysis of baby food. Highlights: IC-MS/MS method for determination of ethephon, HEPA, chlorate, and perchlorate. Quantification at a RL of 0.010 mg/kg in plant-derived commodities. Extension of limited dynamic range of chlorate and perchlorate by ILIS analogues. Method validation in six representative plant-derived commodities.